Hardware Virtualization on Coarse-Grained Reconfigurable Architectures - Lo, Thiago Berticelli; Carro, Luigi; Beck, Antonio Carlos Schneider (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
Even though reconfigurable systems have already proven to be an alternative to speedup embedded applications with reduced energy costs, because of their adaptability and high flexibility, their use result in a significant overhead in chip area. Therefore, this work addresses this issue by the use of the hardware virtualization technique, using a coarse-grained reconfigurable array as study case. We explore two different virtualization alternatives, achieving a reduction in area of up 96%, with marginal performance loss comparing to the original architecture.